Extracellular Nucleophosmin Is Increased in Psoriasis and Correlates With the Determinants of Cardiovascular Diseases - D'Agostino, Marco; Beji, Sara; Sileno, Sara; Lulli, Daniela; Mercurio, Laura; Madonna, Stefania; Cirielli, Corrado; Pallotta, Sabatino; Albanesi, Cristina; Capogrossi, Maurizio C.; Avitabile, Daniele; Melillo, Guido; et al. (Frontiers in Cardiovascular Medicine, 2022)
We previously showed that genotoxic stress induced an active extracellular release of nucleophosmin (NPM) in human cardiac mesenchymal progenitor cells, and that serum deprivation provokes NPM secretion from human endothelial cells, eliciting inflammation via nuclear factor kappa B (NF-kB) transcriptional activation. Herein, we wanted to determine whether NPM was similarly modulated in skin and plasma of psoriatic patients (Pso). We found that NPM was induced in 6 skin biopsies compared to 6 normal skin and was markedly increased in lesional (LS) versus non-lesional skin (NLS) biopsies. Moreover, NPM was also increased at the transcriptional levels in LS vs NLS. Both the innate stimuli, such as lipopolysaccharides and Poly inositol-cytosine and adaptive stimuli, i.e. cytokine mix, were able to induce extracellular release of NPM in immortalized keratinocytes and human skin fibroblasts in absence of cytotoxicity. Interestingly, NPM interacts with Toll like receptor (TLR)4 in these cells and activates a NF-kB-dependent inflammatory pathway upregulating interleukin IL-6 and COX-2 gene expression. Finally, circulating NPM was increased in the plasma of 29 Pso compared to 29 healthy controls, and positively correlates with psoriasis area severity index (PASI) and with determinants of cardiovascular diseases (CVDs), such as, pulse wave velocity, systolic pressure and left ventricular mass. Further, NPM positively correlates with miR-200c circulating levels, that we previously showed to increase in Pso and to correlate with CVD progression. Our data show that circulating miR-200c is physically associated with extracellular NPM, that most probably is responsible for its extracellular release and protection upon cytokine mix via a TLR4-mechanism. In conclusion, NPM is increased in psoriasis both in skin and in plasma and might be considered a novel biologic target to counteract chronic inflammation associated with CVD risk.